OPTIMIZATION OF ONLINE PLATFORM DURING COVID-19 PANDEMIC ADOPTED BY LECTURERS AT STIT AL AZIZIYAH - Dedy Ahsan Muttaqin (eJurnal Al Musthafa, 2022)
This research is motivated by the situation covid-19 pandemics. The existence of various limitations of human resources, study space, and time to face-to face to experience various obstacles to achieve optimal result. Online platform is one of several alternative effort to improve the quality of teaching and learning during covid-19 pandemic. Through online platform, students and lecturers can interact in learning across distance, time and space. The objectives of this study were to obtain an overview of the online platform during covid-19 pandemic at STIT Al Aziziyah Kapek Gunungsari. The data were obtained from students STIT Al Aziziyah Kapek Gunungsari by observation, interview and questionnaire. The result of this study showed that the students’ digital literacy, independence, critical thinking, and retaining information using online platform at STIT Al Aziziyah Kapek Gunungsari was improved through significantly during covid-19 pandemics.